DETERMINASI PERSISTENSI LABA PADA PERUSAHAAN DI INDONESIA - Dessica Ariyanti, (2021)
This study aims to determine empirically the effect of sales volatility, market concentration, cash flow volatility, audit fees, debt levels and company size as control variables on earnings persistence in property and real estate sub-sector companies listed on the Indonesia Stock Exchange 2015-2019 period. The sample was selected by purposive sampling method and collected 125 data samples. Hypothesis testing in this study uses Multiple Linear Regression Analysis with the SPSS version 25 program and a significance level of 5% (0.05). The results of this study indicate: 1) market concentration and cash flow volatility have a significant positive effect on earnings persistence; 2) audit fees have a significant negative effect on earnings persistence; 3) sales volatility and debt levels do not have a significant effect on earnings persistence in property and real estate sub sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period.